Long-term follow-up for patients with colonic perforation due to colonoscopy: From clinical and medicolegal viewpoints - Tzu-Chun Chen; Ji-Shiang Hung; Been-Ren Lin; John Huang; Jin-Tung Liang (Formosan Journal of Surgery, 2017)
Background: This retrospective study analyzes the clinicopathologic features and medicolegal debates on this complication. Methods: There were 29 records of colonic perforations, whose charts were retrospectively reviewed. Results: A total of 26 perforations occurred as a result of diagnostic colonoscopy, and three occurred after therapeutic colonoscopy. Eight perforations were diagnosed immediately during the procedure, based on the revelation of intraperitoneal organs with bleeding of bowel wall on the colonoscopic monitor. Twenty patients were diagnosed as a hollow-organ perforation within 12 h after the completion of colonoscopy, whereas one perforation was found more than 24 h after colonoscopy. Abdominal pain and distention are the most common symptoms. All the patients underwent emergency surgery. One patient had wound infection, and two patients had leakage of the repair site. One patient aged 80 died of pulmonary septic complication. Our hospital paid all additional expenses which were not covered by the National Health Insurance Bureau for all patients, ranging from 500.0 to 1500.0 US dollars (mean ± standard deviation, 549.0 ± 145.0 US dollars). Four patients (13.8%) asked for further compensation of the complication and one litigated. Conclusions: Iatrogenic colonic perforation due to endoscopy is potentially lethal, especially for aged patients. Some patients and their family viewed the perforation as malpractice and asked for compensations. Usually, the primary repair of the perforation site is safe, and long-term follow-up reveals no sequelae after adequate treatment.